Adolescent romantic competence and parenting attitudes: Gender variations and correlates. (June 2017) - Shulman, Shmuel; Scharf, Miri; Bohr, Yvonne; Tuval-Mashiach, Rivka; Hirsh, Yuval; Faians, Maya
The current study examined the distinctive gender-related expressions of adolescent romantic competence and patterns of maternal and paternal attitudes toward daughters' and sons' romantic involvements. Employing a qualitative approach, an in-depth interview assessing romantic competence was given to 69 Israeli adolescents (37 boys) ranging in age from 15 to 18 years, M = 16.74 ( SD = .81). In addition, parents were interviewed regarding their attitudes toward their adolescents' romantic involvements. Findings indicated that girls exhibited greater romantic maturity and their accounts of romantic involvements were more coherent, compared to boys. Romantic agency did not differ across gender. Mothers and fathers reported similar levels of supportive attitude toward offspring's romantic involvement. However, in depth reading of parents' motives suggested that fathers had a supportive attitude toward their sons' romantic and sexual experimentation, while mothers' supportive attitude was aimed at enhancing romantic intimacy in both genders. In addition, mothers were found to have a more protective attitude toward their daughters than toward their sons. Examining associations between parental attitudes and adolescent romantic competence showed that maternal, not paternal, supportive attitude was associated with greater romantic competence in both genders. In addition, maternal protective attitude was associated with girls' involvement in more stable relationships, while fathers' protective attitude was adversely associated with daughters' romantic agency. Findings suggest that the attitudes of both parents reflect, to some extent, the more traditional scripts of gender relationships.